2009
DOI: 10.2174/092986709787002691
|View full text |Cite
|
Sign up to set email alerts
|

Senescence and Cell Death Pathways and Their Role in Cancer Therapeutic Outcome

Abstract: Anticancer drug-induced tumor suppression may involve mechanisms of protection against neoplastic transformation that are normally latent in mammalian cells and consist in a genetic program implemented during anti-tumoral defense. This defense program results in the self elimination of cells harboring potentially dangerous mutations by triggering cell death through apoptosis and/or autophagy or in the execution of a program that leads to a permanent growth arrest known as senescence. These responses are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Apoptosis is an evolutionarily conserved cell suicide process elicited by physiological, pharmacological and pathological conditions. The initiation and execution of apoptosis depends on the activation of the extrinsic and/or intrinsic death pathways (28,29). Extrinsic or death receptor pathways are associated with death receptors, such as FAS, the TRAIL receptor (TRAIL-R) and TNF receptor (TNF-R).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is an evolutionarily conserved cell suicide process elicited by physiological, pharmacological and pathological conditions. The initiation and execution of apoptosis depends on the activation of the extrinsic and/or intrinsic death pathways (28,29). Extrinsic or death receptor pathways are associated with death receptors, such as FAS, the TRAIL receptor (TRAIL-R) and TNF receptor (TNF-R).…”
Section: Discussionmentioning
confidence: 99%
“…Cell senescence is usually characterized by a large and flattened morphology, an increase in intracellular granules and elevated SA-β-gal activity (30). Similar to apoptosis, cell senescence plays a crucial role in suppressing tumorigenesis and may contribute to the outcome of cancer therapy (29)(30)(31)(32). It has been shown that chemotherapeutic agents, such as cisplatin, doxorubicin, SN-38 and camptothecin, inhibit the growth of tumors via cell senescence (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, also described as type Ⅱ programmed cell death, is constitutive in all types of cells containing a lysosomal compartment. This housekeeping function is involved in cytoplasmic homeostasis because it controls the turnover of long-lived proteins and probably also the remodeling of the cytoplasm [13][14][15] . Beclin1 is a 60 kDa coiled-coil protein, and forms a protein complex with a phosphatidyl insositol-3-kinase (PI3K) within the autophagosome [16] .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] So, next, the effects of AECA on cell apoptosis and cell cycle distribution in LS-174-T cells were determined by flow cytometry analysis. As shown in Figure 3, apoptosis was detected in LS-174-T cell following 72 hours of exposure to various doses of AECA in a dose-dependent manner and compared with the controls ( p < 0.05).…”
Section: Aeca Inhibits Colony Formation Of Ls-174-t Cellsmentioning
confidence: 99%